Pengaruh Pendidikan Kesehatan Melalui Audiovisual Terhadap Peningkatan Pengetahuan Ibu Tentang Penanganan Demam Pada Anak Usia 0-2 Tahun Dengan Metode Tepid Water Sponge - Kuloh, Abdul Basri; Jamaludin, Raihan; Kadang, Yulta (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2024)
Fever is an increase in body temperature above the normal range due to infection or inflammation. Non-pharmacological treatments to reduce fever in children are sometimes often forgotten by parents, in this case mothers, one of which is tepid water sponge. Lack of knowledge of mothers related to non-pharmacological management of fever in children results in improper management, resulting in less than optimal healing process. The purpose of this study was to determine the effect of health education through audiovisual on the level of maternal knowledge about fever management in children 0-2 years using tepid water sponge at Puskesmas Tambelang, Bekasi Regency. This research method uses Quasi-experimental designs (one group pretest-posttest). The sample in this study amounted to 94 mothers who had children aged 0-2 years at the Tambelang Health Center, Bekasi Regency. Samples were taken using cluster random sampling technique. Data collection using a questionnaire sheet on knowledge of handling fever using tepid water spong. Data analysis using the Wilcoxon test. The results of the statistical test showed that there was an effect of health education through audiovisual on the level of maternal knowledge (sig.0.000 <0.05). The conclusion is that there is an effect of health education through audiovisual on the level of knowledge of mothers about handling fever in children aged 0-2 years using tepid water sponge at the Tambelang Health Center, Bekasi Regency. Suggestions are expected to increase the implementation of health education to mothers who have children, related to handling fever in children using tepid water sponge.